Ethical behavior of marketing managers - Fritzsche, David J. (Journal of business ethics, 1983)
The ethical behavior of marketing managers was examined by analyzing their responses to a series of different types of ethical dilemmas presented in vignette form. The ethical dilemmas addressed dealt with the issues of (1) coercion and control, (2) conflict of interest, (3) the physical environment, (4) paternalism, and (5) personal integrity. Responses were analyzed to discover whether managers' behavior varied by type of issue faced or whether there is some continuity to ethical behavior which transcends the type of ethical problem addressed.